Parents and primary care physicians have different views about copying medical letters to parents after paediatric outpatient visits. (15th August 2014) - Cachat, Francois; Marques‐Vidal, Pedro; Girardin, Eric; Chehade, Hassib; Piot‐Ziegler, Chantal
Abstract Aim We assessed how satisfied parents were when they received a copy of the letter sent to their primary care physician after their child attended a hospital outpatient clinic and compared their views with those of the primary care physician. Methods Anonymised questionnaires were sent to parents, and their primary care physician, after their child had visited a paediatric nephrology unit. Results We received responses from 112 parents (46%) and 69 primary care physicians (93%). Most parents (97%) were satisfied with the process, 94% thought that the letter was a true reflection of the outpatient consultation and easy to understand, and 55% read it to their child. However, 21% would have preferred a simpler letter. More than a third (37%) of the primary care physicians did not approve of the parents being sent the letter, and 30% felt that the letter was difficult for the parents to understand and should be replaced with a simpler letter. Conclusion Most parents (97%) appreciated receiving a copy of the letter following their child's outpatient clinic visit, and 95% understood its contents. More than half (55%) read the letter to their child. However, 37% of primary care physicians did not approve of the practice.